2012
DOI: 10.1016/j.tet.2011.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sansalvamide A peptidomimetics: triazole, oxazole, thiazole, and pseudoproline containing compounds

Abstract: Peptidomimetic-based macrocycles typically have improved pharmacokinetic properties over those observed with peptide analogs. Described are the syntheses of 13 peptidomimetic derivatives that are based on active Sansalvamide A structures, where these analogs incorporate heterocycles (triazoles, oxazoles, thiazoles, or pseudoprolines) along the macrocyclic backbone. The syntheses of these derivatives employ several approaches that can be applied to convert a macrocyclic peptide into its peptidomimetic counterpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 46 publications
(58 reference statements)
0
59
0
1
Order By: Relevance
“…These data indicated that the backbone conformation was negatively impacted by rigid moieties such as the oxazole. Alternative heterocycles including triazoles and pseudoprolines had the same impact on the biological activity of the molecules demonstrating that the loss of potency was likely due to altering the macrocycles conformation [29]. Supporting these data is the loss or gain of activity when the stereochemistry of an amino acid in the backbone is altered from d to l or vice versa.…”
Section: Sansalvamide Amentioning
confidence: 83%
See 1 more Smart Citation
“…These data indicated that the backbone conformation was negatively impacted by rigid moieties such as the oxazole. Alternative heterocycles including triazoles and pseudoprolines had the same impact on the biological activity of the molecules demonstrating that the loss of potency was likely due to altering the macrocycles conformation [29]. Supporting these data is the loss or gain of activity when the stereochemistry of an amino acid in the backbone is altered from d to l or vice versa.…”
Section: Sansalvamide Amentioning
confidence: 83%
“…However, although the inclusion of an oxazole moiety into the SM145's scaffold (Fig. 2) reduced the rings flexibility, it did not have any cytotoxicity [29]. These data indicated that the backbone conformation was negatively impacted by rigid moieties such as the oxazole.…”
Section: Sansalvamide Amentioning
confidence: 96%
“…The relative cytotoxicity of the heterocycle analogs was rationalized on their ability to adopt backbone conformation and side chain presentations similar to the native peptide. [68]. 6 µM) (Fig.…”
Section: Thiazole Influences Conformation In Peptidomimeticsmentioning
confidence: 99%
“…10). [68] Replacement of the Leu-Val residue with thiazole (73) gave an analog with equal cytotoxicity to the parent sansalvamide A (72). The relative cytotoxicity of the heterocycle analogs was rationalized on their ability to adopt backbone conformation and side chain presentations similar to the native peptide.…”
Section: Thiazole Influences Conformation In Peptidomimeticsmentioning
confidence: 99%
“…This sequence produced two tripepetides (13 and 14) and a tetrapeptide (16) with a terminal isopentyl ester and a free amino substituent, ready for peptide coupling with a fullerenyl amino acid. The synthesis of the peptide moieties containing an oxazole terminus started with the synthesis of 17 by reported methods [22] (Scheme 2). This oxazole 17 then underwent a typical coupling with N,N'-diprotected forms of either L-Arg or D-Lys to produce 18 and 19, which were deprotected to the free amines 20 and 21, respectively.…”
Section: Chemistrymentioning
confidence: 99%